Translations as Shapers of Image: Don Carlos Darwin and his Voyage into Spanish on H.M.S. Beagle - Paoletti, Elisa (TTR, 2005)
AbstractWhen we think about Charles Darwin, we usually associate him with his theory of evolution and his masterpiece, The Origin of Species. There is a lesser known, younger Darwin who, at 22 years of age, travelled around the world and poured his insightful observations in a very popular travel account, The Voyage of the Beagle. A considerable part of Darwin’s journal was dedicated to South America and, interestingly, it was in the Spanish-speaking regions he visited that he was called “Don Carlos.” This article presents an analysis that will revolve around three translations of The Voyage of the Beagle into Spanish. Their different translation projects will be described case by case and will be finally studied either from a “seer” or a “seen” point of view, which will be closely related to the place of publication and the content included in each translation. We will see the Spanish publishers taking a “seer,” a visitor approach while the South American publishers lean to the “seen,” the visited side and adapt the content of Darwin’s account as a young fledgling scientist accordingly. The different approaches adopted by each of these projects emphasize different traits of Darwin’s image and contribute to its construction in the Spanish-speaking world.